THE PROBLEM OF WILL: PSYCHOLOGICAL, PEDAGOGICAL AND CARITATIVE SOCIAL ASSESSMENT - Alksne, Antra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Modern science proves that new psychological patterns that come to existence in early childhood, have an unchanging significance in developing abilities and shaping personality. Learning of social, moral norms relates to family which is influenced by historical, ethno-cultural, socio-cultural and socio-economic environment. Other persons play an important role in setting goals by their personal example. Action reveals the personality of man guided by certain motivation and striving towards defined, true goals. The purpose of the article is to further understanding of the role of will in shaping human personality. The reference literature researches the mechanism and reasons of formation of individual’s will. The basis of this paper consists of conclusions from the works of A.Augustins, A.Rubenis, A.Dannenfelde (anthropological aspect), V.Renge, J.Piaget, A.Abele and other authors (psychological aspect), D.Albrecht, A.Kuznetsova, R.Jansone and other known authors (pedagogical aspect). It is important for the person to be willing to establish his/her fundamental guidelines. Personality possesses its own vitality, creative character that is able to make a conscious choice and act responsibly in order to strengthen the ties with itself, social environment and God. Neither mind of soul, nor will are positioned in the spiritual world.